Theta oscillation and neuronal activity in rat hippocampus are involved in temporal discrimination of time in seconds - Nakazono, Tomoaki; Sano, Tomomi; Takahashi, Susumu; Sakurai, Yoshio (Frontiers in Systems Neuroscience, 2015)
The discovery of time cells revealed that the rodent hippocampus has information of time. Previous studies have suggested that a role of hippocampal time cells is to integrate temporally segregated events into a sequence using working memory with time perception. However, it is unclear that hippocampal cells contribute to time perception itself because most previous studies employed delayed matching-to-sample tasks that did not evaluate time perception separately from working memory processes. Here, we investigated the function of the rat hippocampus in time perception using a temporal discrimination task. In the task, rats had to discriminate between durations of 1 and 3 sec to get a reward, and maintaining task-related information as working memory was not required. We found that some hippocampal neurons showed firing rate modulation similar to that of time cells. Moreover, theta oscillation of local field potentials (LFPs) showed a transient enhancement of power during time discrimination periods. However, there were little relationships between the neuronal activities and theta oscillations. These results suggest that both the individual neuronal activities and theta oscillations of LFPs in the hippocampus have a possibility to be engaged in seconds order time perception; however, they participate in different ways.